If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 2n = 4n + 2 Reorder the terms: 6 + 2n = 2 + 4n Solving 6 + 2n = 2 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 6 + 2n + -4n = 2 + 4n + -4n Combine like terms: 2n + -4n = -2n 6 + -2n = 2 + 4n + -4n Combine like terms: 4n + -4n = 0 6 + -2n = 2 + 0 6 + -2n = 2 Add '-6' to each side of the equation. 6 + -6 + -2n = 2 + -6 Combine like terms: 6 + -6 = 0 0 + -2n = 2 + -6 -2n = 2 + -6 Combine like terms: 2 + -6 = -4 -2n = -4 Divide each side by '-2'. n = 2 Simplifying n = 2
| -10t=-18-19t | | 4t+48n=100 | | 5(0-4)-9=3-2(0+16) | | 2a+6=a+2 | | 5X-13=15+17x | | 3=7x^2+5 | | (25b-7)-6(4b+4)=-6 | | (5b-1)(3b+2)= | | 14/2=x | | -5-7(1+8z)=30 | | -3d-4+9d=16 | | 4x^12-5x^6-14=0 | | 3n+3-4= | | -2(-9m-2)-1=27+10 | | 4x-18=8(x+6) | | -12+3b=-6+2b | | -3/x=6 | | (8a+3b-9)+(-17a-2b+8)= | | 2(4x-3)-8=1+2x | | 7a-1=5a+13 | | 2=.2x-.4x-7 | | 2=.02x-0.4x-7 | | -27+3n=2(7n+4) | | 2n+4=-3n+14 | | -7(p+8)=2 | | 8x+2(x+6)=2x+15 | | (7b-6)-3(2b+4)=-3 | | 1/3x^2-1/18x-11/9=0 | | -2(k+16)=-44 | | e^2k=6 | | 15=-7+9(v-6) | | 30(1/2) |